(3cJGH jJVef PcQ eG jdJReg GdJGFH ef CYeGd hCMhGd JhLH dg GdKHGJ aj ebGegs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hMOg CeG HYO abO hUdfG cJGHce hYdefG eG ajgG hde fQi ajgG eG jbJVi LhGHkG jchf UhGHkG s
(3BNQgG (B:s
(3hNaV GdLfGM hdjf GdLGfH hSdGeI GdUOQ hGdeYGjH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs